PREDICTING PLANE TRAFFIC WHILE TAKEOFF AND LANDING USING QUEUE MODEL AS THE MEASUREMENT OF ATC SERVICE LEVEL AT ADISUTJIPTO INTERNATIONAL AIRPORT YOGYAKARTA - Hasrul Saleh; Indro Lukito (Journal of Industrial Engineering and Halal Industries, 2020)
This research aims to know the number of air plane traffic increase at Adisutjipto International Airport Yogyakarta until 2025, to know the average number of air plane traffic during rush hour at Adisutjipto International Airport Yogyakarta, and to know the service level of Air Traffic Control towards the air plane when takeoff and landing at Adisutjipto International Airport Yogyakarta.  The researcher used Microsoft Excel and manual calculation in processing the data. The research results showed that the estimation of the number of plane traffic at Adisutjipto International Airport Yogyakarta experienced increase in 2018 with total plane traffic 78376 until 2025 it will increase with total plane traffic reaching 103209. The average number of air plane traffic when takeoff and landing at Adisutjipto International Airport Yogyakarta reach 9 planes in one hour. The service level of ATC at normal condition obtained result 15% while during rush hour reach 80%. The average number of air plane queueing at normal condition is 1 air plane per hour while during rush hour is 3 air planes per hour. The average number of air plane in the system during normal condition is 1 air plane per hour, while during rush hour is 4 air planes. The average time spent for waiting for the queue at normal condition is 4,57 minutes/air plane, while during rush hour reached 16 minutes/air plane. The average time spent for waiting in the system during normal condition is 8,57 minutes/air plane, while during rush hour is 20 minutes/air plane.Kata Kunci : Queue, Takeoff, Landing, Air Traffic Control, Air Plane